Role of "Video Assisted Lecture" on Changing Albanian Undergraduate Students' Opinion Regarding Pain-free Dental Injections in Children - Dorjan Hysi; Esber Caglar; Etleva Droboniku; Celjana Toti; Enida Petro; Onder Kuscu (University of Zagreb. School of Dental Medicine, 2018)
Aim: To evaluate the effectiveness of video assisted lecture in changing the opinions of dental students toward pain-free dental injections in children. Methods: The fifth-year students (n:62) of University of Medicine of Tirana, Faculty of Dental Medicine participated in the study. The study was conducted in two stages: first a Theoretical lecture (Stage 1), "Pain-free Local Analgesia Techniques in Children" was provided, and was followed by a second lecture supported by video recordings of real clinical cases (Stage 2). Students' opinions were evaluated by means of a short survey administered before the lectures, after the theoretical lecture, and after the video assisted lecture. Results: Before the study, only 47.9% of students believed in the possibility (agree and definitely agree) of pain-free local anesthesia in children, whereas after the study, the percentage had risen to 67.7% (p=0.0001). Baseline opinions of students changed significantly after the video-assisted lecture (p=0.0001). However, there is no statistical difference between mean scores of theoretical lecture (Stage 1) and video-assisted lecture (Stage 2). Conclusions: Theoretical lecture (Stage 1) was found to be significantly effective in changing the opinions regarding "Pain-free dental injections in children," however, a video based dental education (Stage 2) was found to be relatively effective in supporting the change in dental students' opinion.